2013
DOI: 10.1590/s1516-14392013005000016
|View full text |Cite
|
Sign up to set email alerts
|

Rutting analysis of 100 mm diameter polypropylene modified asphalt specimens using gyratory and Marshall compactors

Abstract: Compaction technique used in Marshall design does not model the process of actual rolling procedures on site exactly. Carrying out laboratory compaction of dense bituminous mixtures with Superpave gyratory compactors is a more realistic way of simulating actual compaction. In this study, mechanical differences of reference and polypropylene modified asphalt mixtures were compared using Superpave gyratory and Marshall compaction methods by carrying out repeated creep tests utilising universal testing machine. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Additionally, in order to obtain the internal structure of samples comparable to roller compaction, the compaction angle parameter should be appropriately selected, slightly higher than that specified by technical regulations. Taking into account the resistance to rutting, Tapkin and Keskin demonstrated that the samples made in the gyratory press were less susceptible to permanent deformations than those compacted using the Marshall method [18]. Lee et al found that in case of crumb rubber asphalt mixes air void content was significantly dependent on the number of gyratory rotations and directly related to this rutting increased along with air voids [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in order to obtain the internal structure of samples comparable to roller compaction, the compaction angle parameter should be appropriately selected, slightly higher than that specified by technical regulations. Taking into account the resistance to rutting, Tapkin and Keskin demonstrated that the samples made in the gyratory press were less susceptible to permanent deformations than those compacted using the Marshall method [18]. Lee et al found that in case of crumb rubber asphalt mixes air void content was significantly dependent on the number of gyratory rotations and directly related to this rutting increased along with air voids [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that in Marshall compaction method load is perpendicular to compaction axis and relies on falling weight which does not properly simulate field compaction. Thus, recently Marshall compactor has been losing popularity in pavement laboratories in comparison with gyratory compactor [33].…”
Section: Optimum Asphalt Contentmentioning
confidence: 99%
“…In the past 20 years, China’s traffic has been developing towards “large flow, heavy axle load, high tire pressure”, and some disadvantages of the Marshall method have become obvious [ 10 , 11 , 12 ]. The SMA pavements designed by the Marshall method with early ruts, oil spills, and water seepage indicate that the Marshall compaction standard cannot meet current traffic requirements [ 9 , 13 , 14 , 15 ]. In addition, the Marshall specimen has a poor correlation with the mechanical properties of the site so that the test indicators of the specimen produced by the Marshall method in the laboratory cannot determine the quality of the field pavement very well [ 9 , 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%